Does measuring quality of delivery for a parent led intervention to treat ADHD in children explain individual variation in outcome? - Thompson, Catherine (2025)
Introduction: Parent led interventions (PLI) to treat Attention Deficit/Hyperactivity Disorder in children were not found to be effective for ADHD symptoms from non-blinded reports compared with controls. In addition apart from baseline child symptom severity, no factors consistently explained for whom these interventions are effective and why. One reason for individual variation in outcome could be quality of delivery measured in real time. This study developed and applied a bespoke measure of “quality of delivery” to explore this. It was applied to all subjects of the New Forest Parenting Programme arm of the Comparison of Preschool Parenting Interventions (COPPI) trial (n=133).